Pengaruh Kepatuhan Wajib Pajak dan Penerima Pajak Bumi dan Bangunan Terhadap Pendapatan Asli Daerah Kota Jambi - Marsela, Marsela; Mutia, Agustina (Gapenas Publisher, 2025)
This study aims to analyze the effect of taxpayer compliance and Land and Building Tax (PBB) revenue on the Regional Original Revenue (PAD) of Jambi City. This research employs a quantitative approach using Partial Least Square (PLS) analysis. The data consist of primary data collected through questionnaires from 100 land and building taxpayers and secondary data obtained from the BPPRD of Jambi City for the period 2022–2024. The results indicate that taxpayer compliance has a significant effect on PAD, where increased compliance can drive the optimization of regional revenue. In addition, PBB revenue also has a positive effect on PAD, although additional strategies are required to maintain effective tax collection performance